Strategi Kampanye Digital dan Perubahan Pemilih Pemula: Studi Kasus Prabowo-Gibran di Pilpres 2024 - Rifqi Fadhlurrohman (STISIPOL Raja Haji, 2026)
The rapid development of digital technology has transformed political campaigning, particularly among first-time voters in Indonesia. This study examines the digital campaign strategies of the Prabowo–Gibran presidential ticket in the 2024 election and analyzes their influence on young voters’ political behavior. Using a qualitative approach, primary data were collected through in-depth interviews with campaign actors and political communication observers, supported by documentation and digital content analysis. The findings indicate that the campaign relied heavily on social media platforms such as TikTok, Instagram, and Twitter, accompanied by big data–based audience segmentation to personalize political messages. The use of relational engagement and responsive campaigning strengthened emotional attachment, expanded reach, and improved interaction between candidates and young voters. However, several challenges emerged, including the risk of information distortion and difficulties in maintaining message consistency within a highly dynamic digital environment. This study contributes to the growing literature on digital political communication by demonstrating how strategic content production and data-driven targeting shape the preferences and participation of first-time voters in contemporary Indonesian elections.